The relationship between endowment and ownership effects in memory across cultures - Collard, Philip; Walford, Alexandra; Vernon, Lucy; Itagaki, Fumihiko; Turk, David (Consciousness and cognition, 2020)
•A novel protocol for measuring an endowment bias (EB) is developed.•UK participants showed EB scores consistent with the typical endowment effect.•Their EB scores correlated with scores for the self-reference effect in memory.•Japanese participants showed no EB.•No correlation was found for their EB scores and the self-referential effect. An object one owns is typically more highly valued than an equivalent object owned by another person. This endowment effect has been attributed to the aversion of loss of one’s possessions (through selling), or the added value of an item due to self-association (through owning). To date, investigation of these mechanisms has been hampered by the between-subjects methodology traditionally employed to measure endowment. Over two experiments, we report a novel within-subjects method for measuring an endowment bias. In these studies, Western participants showed enhanced valuation of owned items, whereas East-Asian participants did not. This endowment bias also correlated with the ownership effect in memory (a measure of self-referential processing) in Western, but not East-Asian participants. Our results suggest that the endowment effect is partly predicated on the same factors that influence the ownership effect and that this commonality is likely linked to conceptions of ownership specifically, and self-concept more generally.